PENDIDIKAN YANG AMAN PADA MASA PANDEMI COVID-19 - Arif Wicaksono; Arina Nurfianti (Universitas Tanjungpura, 2022)
Coronavirus Disease 2019 (COVID-19) pandemic hit in 2020. This pandemic was causing changes in almost all sectors in our life, including education. Most of the education carried out in Indonesia uses the direct / face-to-face/ offline method between educators and students. The spread of COVID-19 is through direct contact or contact with air or surface containing the virus. The unevenness of perceptions, examinations, and existing protocols causes fear of face-to-face education. This research is a review of articles on COVID-19, health and education protocols during the COVID-19 pandemic. Public perceptions including educators, students and families about COVID-19 must be equalized to fight the pandemic together and welcome online education which is the safest option in education during pandemic. AbstrakTahun 2020 terjadi pandemi Coronavirus Disease 2019 (COVID19). Pandemi ini menyebabkan perubahan di hampir semua bidang, termasuk pendidikan. Pendidikan yang dilakukan di Indonesia banyak yang menggunakan cara langsung/tatap muka antara pendidik dan peserta didik. Penyebaran COVID-19 adalah melalui kontak langsung atau bersentuhan dengan barang-barang yang mengandung virus. Belum meratanya persepsi, pemeriksaan, dan protokol yang ada menyebabkan ketakutan untuk melakukan pendidikan secara tatap muka. Penelitian ini merupakan telaah artikel mengenai COVID-19, protokol kesehatan dan pendidikan selama masa pandemi COVID-19. Persepsi masyarakat termasuk pendidik, peserta didik dan keluarga mengenai COVID-19 harus disamakan untuk bersama melawan pandemi dan menyambut pendidikan secara daring yang merupakan pilihan paling aman dalam pendidikan pada masa pandemi.